Physical Fitness of Prison Officers - Józef Bergier; Leszek Wojciechowski (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2018)
The objective of the study was to investigate the career-choice motives for one's entering the prison service as an operational officer, and the level of physical fitness. The study was conducted in April 2015, and included 100 officers employed in Biała Podlaska prison. The examined group consisted of 93 males; aged 23-52; mean age 37.2, and 7 females aged 3-43; mean age 37.7 (30-43). 61 (61%) of the males were employed as security guards, while 39 persons (39%), including 7 females, as clerks in the administration section. The study methods included: a physical fitness test consisting of 5 physical performance tests, recommended by the regulation of the Minister of Justice, the International Physical Activity Questionnaire(IPAQ) - long-form, questions designed by the author of the paper. Career-choice motives turned out to be conditioned purely be economic incentives and the professions' stability as opposed to other professional specialties. The respondents were fit and engaged in numerous physical activates. The factors which significantly determined the level of one's fitness depended on: age, education, a high self-report on physical fitness, total physical activity and the number of done sports. Originality of the study is based on investigating the condition of physical fitness of prison officers with the use of currently recommended assessment methods in Poland.